The Declining Trend of Religious Films in Indonesia: Can They Win Again? Tren Yang Menurun Dari Film Indonesia Bergenre Religi: Apakah Dapat Kembali Unggul Pada Komunitas Muslim? - Susilo, Daniel; Hidayat, Endik; Mujiono; Dalangin, John Jerico (ETTISAL : Journal of Communication, 2023)
This research investigates the prospects of religious films in Indonesian cinemas and OTT streaming platforms in the post-pandemic era. It addresses the decline in viewership of religious films, particularly in the Jakarta, Bogor, Depok, Tangerang, and Bekasi regions. The study aims to identify the loyal consumers of religious films and propose strategies to reinvigorate their appeal and attract a wider audience. The theoretical framework for analysis is derived from Baudrillard's theory of the consumption society. Utilising qualitative methods, supplemented by survey data from film consumers in the Greater Jakarta area, this study examines the distinct market segmentation of religious films, albeit with relatively lower enthusiast numbers compared to other film genres in OTT and electronic cinema. To regain competitiveness, religious films could be creatively blended with other genres, such as religious comedy, to offer a more dynamic and inclusive experience, steering away from a rigid focus on da'wah content.